Detection of circulating tumor cells in colorectal cancer patients using the GILUPI CellCollector: results from a prospective, single‐center study. Issue 7 (17th June 2019) - Dizdar, Levent; Fluegen, Georg; van Dalum, Guus; Honisch, Ellen; Neves, Rui P.; Niederacher, Dieter; Neubauer, Hans; Fehm, Tanja; Rehders, Alexander; Krieg, Andreas; Knoefel, Wolfram T.; Stoecklein, Nikolas H.
Abstract : The GILUPI CellCollector (CC) is a novel in vivo circulating tumor cell (CTC) detection device reported to overcome the limitations of small blood sample volumes. The aim of this prospective, blinded study was to evaluate the clinical application of the CC and to compare its performance to the CellSearch (CS) system in M0 and M1 colorectal cancer (CRC) patients. A total of 80 patients (31 M0, 49 M1) with CRC were enrolled. CTCs were simultaneously measured in the peripheral blood using CS and the CC, and the results of both assays were correlated to clinicopathological variables and overall survival. The total number of detected CTCs and CTC‐positive patients did not significantly differ between both assays. In the M0 patients, the CC detected CTCs more frequently than CS. There was no significant difference in total CTC numbers detected with the CC between M0 and M1 patients. In addition, no significant correlation with clinicopathological parameters or overall survival was observed with CC CTCs. In contrast, detection of CTCs with CS was significantly correlated with Union for International Cancer Control stage and reduced overall survival. There was no correlation between CTCs detected by the CC and the CS system. Using in silico analysis, we estimate that CC screens a volume of 0.33–18 mL during in vivo application, in contrast to much higher volumes reported elsewhere. In conclusion, while being safe and easy to use, the CC did not outperform CS in terms of CTC yield or sensitivity. While CTC detection in M0 CRC patients was significantly increased with the CC, the clinical relevance of these CTCs appears inferior to the cells identified by the CS system. Abstract : The GILUPI CellCollector (CC) is a novel in vivo circulating tumor cell detection device reported to overcome the limitations of small blood sample volumes. In our prospective, blinded study, we simultaneously compared its clinical application and prognostic performance with the CellSearch system in colorectal cancer patients. Using in silico analysis, we estimate the blood volume screened by the CC.